Desmopressin for reversal of Antiplatelet drugs in Stroke due to Haemorrhage (DASH): protocol for a phase II double-blind randomised controlled feasibility trial. Issue 11 (10th November 2020) - Desborough, Michael J R; Al-Shahi Salman, Rustam; Stanworth, Simon J; Havard, Diane; Brennan, Paul M; Dineen, Robert A; Coats, Timothy J; Hepburn, Trish; Bath, Philip M; Sprigg, Nikola
Abstract : Introduction: Intracerebral haemorrhage (ICH) can be devastating and is a common cause of death and disability worldwide. Pre-ICH antiplatelet drug use is associated with a 27% relative increase in 1 month case fatality compared with patients not using antithrombotic drugs. We aim to assess the feasibility of conducting a randomised controlled testing the safety and efficacy of desmopressin for patients with antiplatelet-associated ICH. Methods and analysis: We aim to include 50 patients within 24 hours of spontaneous ICH onset, associated with oral antiplatelet drug(s) use in at least the preceding 7 days. Patients will be randomised (1:1) to receive intravenous desmopressin 20 µg in 50 mL sodium chloride 0.9% infused over 20 min or matching placebo. We will mask participants, relatives and outcome assessors to treatment allocation. Feasibility outcomes include proportion of patients approached being randomised, number of patients receiving allocated treatment, rate of recruitment and adherence to treatment and follow-up. Secondary outcomes include change in ICH volume at 24 hours; hyponatraemia at 24 hours, length of hospital stay, discharge destination, early death less than 28 days, death or dependency at day 90, death up to day 90, serious adverse events (including thromboembolic events) up to day 90; disability (Barthel index, day 90), quality of life (EuroQol 5D (EQ-5D), day 90), cognition (telephone mini-mental state examination day 90) and health economic assessment (EQ-5D). Ethics and dissemination: The Desmopressin for reversal of Antiplatelet drugs in Stroke due to Haemorrhage (DASH) trial received ethical approval from the East Midlands—Nottingham 2 research ethics committee (18/EM/0184). The DASH trial is funded by National Institute for Health and Care Research RfPB grant: PB-PG-0816-20011. Trial results will be published in a peer reviewed academic journal and disseminated through academic conferences and through patient stroke support groups. Reporting will be in compliance with Consolidated Standards of Reporting Trials recommendations. Trial registration numbers: NCT03696121 ; ISRCTN67038373 ; EudraCT 2018-001904-12.